2013
DOI: 10.1186/1471-244x-13-126
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with probable HIV dementia in an African population: A cross-sectional study of an HIV/AIDS clinic population

Abstract: BackgroundThe HIV/AIDS infection is common in sub-Saharan Africa and is associated with psychological and neuro- cognitive impairment. These conditions, however, remain largely unrecognized. In this study we aimed to determine the prevalence of probable HIV dementia (PHD) in an HIV clinic population in Uganda and to delineate the factors associated with such impairment in these HIV positive individuals.MethodsSix hundred eighty HIV clinic attendees were surveyed in a cross sectional study. PHD was assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 15 publications
5
65
1
Order By: Relevance
“…When we used the strategy described by Rodrigues et al (9) of shifting the cutoff point of the IHDS to ≤11 to increase the sensitivity up to 75.7% for the detection of less severe neurocognitive impairment, we identifi ed a prevalence of 71.2% (n=79) in our patients; these fi ndings are more consistent with the previously reported literature (11) (30) .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…When we used the strategy described by Rodrigues et al (9) of shifting the cutoff point of the IHDS to ≤11 to increase the sensitivity up to 75.7% for the detection of less severe neurocognitive impairment, we identifi ed a prevalence of 71.2% (n=79) in our patients; these fi ndings are more consistent with the previously reported literature (11) (30) .…”
Section: Discussionsupporting
confidence: 88%
“…The researchers reported a 69% prevalence of neurocognitive disorders. A similar prevalence (64.4%) was reported by Nakku et al (30) , who evaluated the frequency of neurocognitive impairment in 680 HIV patients in Uganda using the IHDS as the instrument of measure.…”
Section: Discussionsupporting
confidence: 79%
“…49,94 Unlike HIV-associated dementia, milder cognitive disorders are not associated with higher HIV viral load and lower CD4 + T-lymphocyte count, but they are associated with previous cardiovascular disease. 49 The prevalence of HAND in LMICs varies, ranging from 6% to 64% in children and adults [99][100][101][102][103][104][105][106] (Table 1). 96 Postulated mechanisms for mild cognitive disorders include direct ART toxicity, chronic immune activation, or immune reconstitution syndrome.…”
Section: Hiv-associated Neurocognitive Disorder (Hand)mentioning
confidence: 99%
“…A paper presented by Cross et al also raised the link between age and the NCD [36]. For against Nakku et al in their work on NCD risk factors in the population of Uganda reported that advanced age and neurocognitive disorders association was not demonstrated [37]. This phenomenon could be explained by certain stressful situations that seniors would face and which we have escaped.…”
Section: Agesmentioning
confidence: 92%